Detection of wet floor surfaces - Hong, Kun (Nanyang Technological University, 2024)
Singapore experiences consistently high annual precipitation levels throughout the year, this leads to a humid climate and surface water accumulation. Wet floors can occur in various built environments due to factors like plumbing leaks, weather conditions, and equipment malfunctions. They can cause safety risks, property damage, and health concerns. Seeking practical solutions and preventive measures is crucial for creating safe and healthy indoor environments.